Epigenome‐wide Association of DNA Methylation in Whole Blood With Bone Mineral Density. (8th May 2017) - Morris, John A; Tsai, Pei‐Chien; Joehanes, Roby; Zheng, Jie; Trajanoska, Katerina; Soerensen, Mette; Forgetta, Vincenzo; Castillo‐Fernandez, Juan Edgar; Frost, Morten; Spector, Tim D; Christensen, Kaare; Christiansen, Lene; et al.
ABSTRACT: Genetic and environmental determinants of skeletal phenotypes such as bone mineral density (BMD) may converge through the epigenome, providing a tool to better understand osteoporosis pathophysiology. Because the epigenetics of BMD have been largely unexplored in humans, we performed an epigenome‐wide association study (EWAS) of BMD. We undertook a large‐scale BMD EWAS using the Infinium HumanMethylation450 array to measure site‐specific DNA methylation in up to 5515 European‐descent individuals ( NDiscovery  = 4614, NValidation  = 901). We associated methylation at multiple cytosine‐phosphate‐guanine (CpG) sites with dual‐energy X‐ray absorptiometry (DXA)‐derived femoral neck and lumbar spine BMD. We performed sex‐combined and stratified analyses, controlling for age, weight, smoking status, estimated white blood cell proportions, and random effects for relatedness and batch effects. A 5% false‐discovery rate was used to identify CpGs associated with BMD. We identified one CpG site, cg23196985, significantly associated with femoral neck BMD in 3232 females ( p  = 7.9 ×   10 −11 ) and 4614 females and males ( p  = 3.0 × 10 −8 ). cg23196985 was not associated with femoral neck BMD in an additional sample of 474 females ( p  = 0.64) and 901 males and females ( p  = 0.60). Lack of strong consistent association signal indicates that among the tested probes, no large‐effect epigenetic changes in whole blood associated with BMD, suggesting future epigenomic studies of musculoskeletal traits measure DNA methylation in a different tissue with extended genome coverage. © 2017 The Authors. Journal of Bone and Mineral Research Published by Wiley Periodicals Inc.